Blood flow dynamics in reconstructed auricles. Issue 4 (September 2013) - Grayson, Samuel; Öberg, Martin; Becker, Magnus; Wollmer, Per; Svensson, Henry; Wikström, Sven-Olof
Abstract Ear reconstruction with autologous rib cartilage is performed in stages. Restitution of blood flow between the separate stages is crucial to obtain a good result. Laser Doppler perfusion imaging (LDPI) and local temperature were measured in reconstructed and normal ears in response to indirect heating. Ten persons who had had a unilateral ear reconstruction were included in the study. At a minimum, 157 days had passed since the last operation. LDPI showed no difference in blood flow between the reconstructed ear and the normal ear, neither before nor after indirect heating. The upper part of the normal ear was slightly cooler than the corresponding part in the reconstructed ear. Indirect heating caused an increase of LDPI-values and temperatures in the upper, middle, and lower part of the ear both in the reconstructed ear and the normal one. Skin blood flow recovers after 3-stage ear reconstruction and shows normal dynamic response upon indirect heating.